Pengaruh Iklan Televisi Dan Label Halal Pada Produk Wardah Terhadap Keputusan Pembelian (Studi Kasus Mahasiswi Universitas Baiturrahmah Padang) - Amrullah, Amrullah; Yulihardi, Yulihardi (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
Intention of this research is to analyst influence of Advertisement Television and Lawful Lable [of] product of wardah to Decision of Purchasing [at] Coed University of Baiturrahmah Padang. This Research represent Quantitative research, Data which [is] used in this research [is] collected primary data from 94 responder [at] Coed University of Baiturrahmah Padang. With method of Probility Samling,Teknik data collecting the used [is] Kuesioner. Result of data analysis seen from result of test by parsial, coefficient and simultan of determinasi. By parsial value of signifakan Advertisement Television ( X1) to Decision of Purchasing ( Y) equal to ( sig = 0,473 > 0,05), and value of t [count/calculate] Advertisement Television ( X1) 0,720 < 1,662 t of[is tables of, dapatb concluded [by] television advertisement [do] not have an effect on signifikan to decision of purchasing of product of Wardah [at] Coed University of Baiturrahmah Padang. Assess Lawful Lable signifikan ( X2) to Decision of Purchasing ( Y) equal to ( sig = 0,045< 0,05), and value of t Lawful Lable hutung ( X2) 2,036 > 1,662 t of[is tables of, can be concluded [by] lawful lable have an effect on signifikan to decision of purchasing of product of Wardah [at] Coed University of Baiturrahmah Padang. Result of examination by simultan value of ( 0,014 < 0,05) F Â value 4,479 and F of[is tables of equal to 2,313.(Fhitung> Ftabel). Matter this means by together ( Variable television advertisement Simultan) and lawful lable have an effect on positive to decision of purchasing [at] Coed University of Baiturrahmah Padang. Later;Then result of determinasi koefisief equal to 0,70%, while the rest 99,3% influenced by other research variableÂ